# Quantum Operator Problem

## Homework Statement

Using [x,eiap]=-ħaeiap show that xneiap = eiap(x-ħa)n

## Homework Equations

[x,eiap]=-ħaeiap
From which it follows that,
xeiap = eiap(x-ħa)

## The Attempt at a Solution

[xn,eiap] = [xxn-1,eiap]
= [x,eiap]xn-1 + x[xn-1,eiap]
= -ħaeiapxn-1 + x(xn-1eiap-eiapxn-1)
= -ħaeiapxn-1 + xneiap - eiap(x-ħa)xn-1

Expanding the original commutator on the LHS and moving the second term to the RHS gives,

xneiap = -ħaeiapxn-1 + xneiap - eiap(x-ħa)xn-1 + eiapxn
= -ħaeiapxn-1 + xneiap + ħaeiapxn-1
xneiap = xneiap Grrrrrrrrrrrrrrrr

Related Advanced Physics Homework Help News on Phys.org
George Jones
Staff Emeritus
Gold Member
From which it follows that,
xeiap = eiap(x-ħa)
So,
$$\left( X - \hbar a \right) = e^{-iaP} X e^{iaP}.$$

Now, raise both sides to the power of $n$.

So,
$$\left( X - \hbar a \right) = e^{-iaP} X e^{iaP}.$$

Now, raise both sides to the power of $n$.
$$\left(X - \hbar a \right)^n = e^{-niaP} X^n e^{niap}.$$

DrClaude
Mentor
$$\left(X - \hbar a \right)^n = e^{-niaP} X^n e^{niap}.$$
Really? Try a simple case first: $(e^{-iaP} X e^{iaP})^2$.

Does this constitute a legitimate proof by induction?:

$$Xe^{iaP} = e^{iaP}(X-\hbar a)$$
$$X^ne^{iaP} = X^{n-1}Xe^{iap} = X^{n-1}e^{iap}(X-\hbar a) = X^{n-2}Xe^{iap}(X-\hbar a) = X^{n-2}e^{iap}(X-\hbar a)^2$$
$$= \dots$$
$$=X^{0}e^{iap}(X-\hbar a)^{n} = e^{iap}(X-\hbar a)^n$$

Really? Try a simple case first: $(e^{-iaP} X e^{iaP})^2$.
Thanks for making me feel stupid by asking if I was serious.

DrClaude
Mentor
Thanks for making me feel stupid by asking if I was serious.
Saying "Really?" was a way to point out politely that you had made a mistake. It surely is better than "Wrong!", no?

George Jones
Staff Emeritus
Gold Member
$$\left(X - \hbar a \right)^n = e^{-niaP} X^n e^{niap}.$$
Because $X$ and $P$ don't commute, this isn't correct. For example, consider $\left(AB\right)^2 = ABAB$. If $A$ and $B$ commute, then the $BA$ in the middle can be written as $AB$, and, consequently, $\left(AB\right)^2 = A^2 B^2$. If $A$ and $B$ do not commute, then this step is not justified.

@DrClaude made the good suggestion of trying $n = 2$, but let's try $n = 3$.
$$\left( X - \hbar a \right)^3 = \left( e^{-iaP} X e^{iaP} \right)^3 = \left( e^{-iaP} X e^{iaP} \right)\left( e^{-iaP} X e^{iaP} \right)\left( e^{-iaP} X e^{iaP} \right).$$
Now, remove the backets.

Does this constitute a legitimate proof by induction?:

$$Xe^{iaP} = e^{iaP}(X-\hbar a)$$
$$X^ne^{iaP} = X^{n-1}Xe^{iap} = X^{n-1}e^{iap}(X-\hbar a) = X^{n-2}Xe^{iap}(X-\hbar a) = X^{n-2}e^{iap}(X-\hbar a)^2$$
$$= \dots$$
$$=X^{0}e^{iap}(X-\hbar a)^{n} = e^{iap}(X-\hbar a)^n$$
A more standard form of an inductive argument would be:

Let $P\left(n\right)$ be the statement $X^n e^{iaP} = e^{iaP} \left( X - \hbar a \right)^n$. Show that $P\left(1\right)$ is true. Show that if $P\left(k\right)$ is true, then $P\left(k+1\right)$ is true.

Usually, an ellipsis does not appear in an argument that uses mathematical induction.

Because $X$ and $P$ don't commute, this isn't correct. For example, consider $\left(AB\right)^2 = ABAB$. If $A$ and $B$ commute, then the $BA$ in the middle can be written as $AB$, and, consequently, $\left(AB\right)^2 = A^2 B^2$. If $A$ and $B$ do not commute, then this step is not justified.

@DrClaude made the good suggestion of trying $n = 2$, but let's try $n = 3$.
$$\left( X - \hbar a \right)^3 = \left( e^{-iaP} X e^{iaP} \right)^3 = \left( e^{-iaP} X e^{iaP} \right)\left( e^{-iaP} X e^{iaP} \right)\left( e^{-iaP} X e^{iaP} \right).$$
Now, remove the backets.

A more standard form of an inductive argument would be:

Let $P\left(n\right)$ be the statement $X^n e^{iaP} = e^{iaP} \left( X - \hbar a \right)^n$. Show that $P\left(1\right)$ is true. Show that if $P\left(k\right)$ is true, then $P\left(k+1\right)$ is true.

Usually, an ellipsis does not appear in an argument that uses mathematical induction.
Ahhh that makes sense now. For practice with proof by induction as you explained it, does this work?

If $[X,P] = i\hbar$ show that $[X,P^n] = nP^{n-1}i\hbar$

Let $C(n) = [X,P^n]$
$~~~~~~C(1) = [X,P] = i\hbar$
$\text{If } C(k) = kP^{k-1}i\hbar \text{ is true,}$
$C(k+1) = [X,P^{k+1}] = [X,P^k]P + P^k[X,P]$
$~~~~~~~~~~~~~~~= (kP^{k-1}[X,P])P + P^k[X,P]$
$~~~~~~~~~~~~~~~= kP^ki\hbar + P^ki\hbar$
$C(k+1) = (k+1)P^ki\hbar$